The Effect of Hole Fraction on Viscosity in Atactic and Syndiotactic Polystyrenes - TAV, CUMALİ; YAHŞİ, UĞUR (SPRINGER/PLENUM PUBLISHERS, 2015)
The non-Newtonian viscosity behavior of atactic and syndiotactic polystyrenes (aPS and sPS), at temperatures from to and pressures up to 30 MPa, was studied using the recently proposed Yahsi-Dinc-Tav model, in particular, the Cross-like model. Viscosity data with shear rates of to were taken from literature at ambient pressure and were reproduced from the Cross-Vogel model at elevated pressures. The viscosities were predicted using the Yahsi-Dinc-Tav model with average absolute deviations of 4.37 % at ambient pressure and 9.63 % at high pressures for aPS and 2.54 % at ambient pressure and 4.79 % at high pressures for sPS. We extended this work to relate the zero shear and the constant shear rate viscosities in terms of the temperature- and pressure-dependent hole fraction using the thermo-occupancy function. The hole fraction (h) was computed from Simha-Somcynsky hole theory. Analytical relationships of specific density and hole fraction in terms of scaled temperature and pressure were constructed for practical purposes. The effects of tacticity of polystyrenes were discussed in terms of the thermo-occupancy function in detail. In particular, the derivative of the logarithm of the viscosities (viscoholibility) was found to decrease with an increasing hole fraction.
Keywords: Atactic and syndiotactic polystyrenes; Constant shear rate viscosity; Hole fraction; Viscoholibility; Simha-Somcynsky; Zero shear viscosity; PRESSURE-DEPENDENCE; VACANCY BEHAVIOR; VISCOUS BEHAVIOR; TEMPERATURE; LINKING; FLOW; TACTICITY; TERMS